How to see yourself as you really are - Lama, Dalali (New York Atria Books, 2008)
How to See Yourself As You Really Are is based on a fundamental Buddhist belief that love and insight work together to bring about enlightenment, like two wings of a bird. It provides a new perspective on the psychological problems of hurting ourselves through misguided, exaggerated notions of self, others, events and physical things. It shows how even our senses deceive us, drawing us into unwise attachments and negative actions that can only come back to haunt us in the future.
Includes bibliographical references (p. 273-274).
Keywords: Enlightenment (Buddhism)